2019
DOI: 10.1016/j.cegh.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

How do multi-modality strategies affect outcomes in T2D using a randomized control trial?

Abstract: A randomized clinical trial to examine the levels of body mass index, fasting blood glucose, blood pressure and glycemic control using multi-modality strategies among adults with type 2 diabetes. Methods: A randomized control trial (RCT), two-arm, prospective, and an interventional was designed with an intervention group (IG) and a control group (CG) using stratified block randomization and triple-blinding. Adults with T2D (N = 200) were randomly assigned to an intervention group (IG, n = 100) and a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The PCS and MSC was most affected among high-risk adults with DN and undergoing hemodialysis. 27 Our study showed that the QOL of the adults with diabetic nephropathy with moderate to advanced CKD was poor. Moderate socioeconomic status, marital life, male gender were found to be associated with higher QOL scores.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The PCS and MSC was most affected among high-risk adults with DN and undergoing hemodialysis. 27 Our study showed that the QOL of the adults with diabetic nephropathy with moderate to advanced CKD was poor. Moderate socioeconomic status, marital life, male gender were found to be associated with higher QOL scores.…”
Section: Discussionmentioning
confidence: 66%
“…The variance of HbAc1 (31.6%) and the variance of the total QOL (30.6%) was determined by age, gender, education, income, duration of illness, and education. 27 Physical functioning, role physical, body pain, vitality, role emotional, social function, role physical, general health and mental health were low. Physical and mental health composites of QOL were higher due to increased energy, emotional wellbeing and work status.…”
Section: Discussionmentioning
confidence: 96%
“…Adults with diabetes mellitus exposed to telephone counselling and the structured had lower body mass index, blood glucose, and cholesterol levels leading to a better quality of life. 32 Other studies show that compliance with medication and appointment keeping was higher than compliance with diet, fluid restriction, exercise and weighing with patient education. 33,34 The nurse-led cardiac rehabilitation program was statistically and clinically significant for efficacy and adherence scores from posttest1 to posttest2 in the intervention group.…”
Section: Discussionmentioning
confidence: 98%